Marketing Services Amidst Competitive Business Environment for MSMEs - Polama Vastarikki (Community Service Akseprin Journal, 2025)
This service seeks to bridge the knowledge gap and execute a comprehensive service marketing strategy (7P) for Micro, Small, and Medium Enterprises (MSMEs) in the service sector of City Y, which has led to their entrapment in unsustainable price competition. The primary issue encountered is the disproportionate emphasis on products and pricing (the traditional 4P's), neglecting the essential components of services, including People, Process, and Physical Evidence. The objective of this program is to deliver comprehensive training and mentorship to enhance service quality, establish distinctive differences, and cultivate customer loyalty through the application of the 7P Service Marketing framework. This service's innovation is the creation of a Customer Journey Simulation-based Service Quality Transformation (SQT) Model for local service MSMEs. The findings indicated a 25% rise in the average customer satisfaction score (CSAT), a 30% enhancement in the adoption of digital feedback systems, and improved service process efficiency, all of which directly bolstered competitiveness and customer loyalty.